Mechanical and Antimicrobial Properties of Low-Density-Polyethylene/Mgo Nanocomposites - Pino-Lopez, E; Zapata-Ramirez, P; Cament-Riveros, A; Loyo-Davila, C; Moreno-Serna, V (John Wiley and Sons Ltd, 2022)
Low-density polyethylene (LDPE) nanocomposites containing magnesium oxide (MgO) nanoparticles are obtained by melt mixing. MgO nanoparticles ca. 29 ± 2 nm are synthesized by sol–gel and organically modified on the surface with oleic acid (Mod-MgO), whose final concentration in the polymers is 3, 5, and 10 wt%. The presence of these nanoparticles did not affect the crystallization process of LDPE. However, Young s modulus increases with 10 wt% of Mod-MgO nanoparticles, rendering higher reinforcement effects with an increase as high as 48%. This affects the elongation at break, which decreases ca. 57% compared to neat LDPE. The storage and loss modulus of the LDPE/MgO and LDPE/Mod-MgO nanocomposites increases at room temperature and low temperatures (−150 to −50°C) compared to neat LDPE. SEM analysis showed that the organic modification of MgO nanoparticles improved their dispersion within the polymer matrix. Nanocomposites present antimicrobial properties against Escherichia coli, reaching an efficiency ca. 53%. © 2022 John Wiley & Sons Ltd.